Nurses' view of their duties in the organ procurement organization sector (Research, Society and Development, 2020)
Objective: Analyze nurses' views on their roles in the Organ Search Organization sector.  Method: The qualitative approach of the descriptive type was used. The data were collected in the Organization for the Search of Organs department with all effective nurses. For the analysis of participants' discourses, the "Content Analysis" technique was used. Results: The employees of the sector are aware of their functions and are exercising according to the established regulations. They act broadly in educational processes, exercising them with quality, although there are organizational and systematic challenges, such as the low number of professionals who burden them, leaving their actions sometimes with low income. To plan, execute, coordinate, supervise and evaluate nursing procedures as well as notify the Central Transplantation Center of the existence of the potential donor, interview the legal guardian of the donor requesting free informed consent are functions that the nurse performs in his work routine. Conclusion: The study suggests that nurses develop teaching and research skills to publicize their activities and can show the importance of organ harvesting for transplants.